1992
DOI: 10.1007/bf00178302
|View full text |Cite
|
Sign up to set email alerts
|

Technetium-99m hexamethyl propylene amine oxine leucocytes in the assessment of disease activity in inflammatory bowel disease

Abstract: The inflammatory activity in 108 bowel segments of 40 patients with suspected or known inflammatory bowel disease was assessed macroscopically by endoscopy, histology and technetium-99m hexamethyl propylene amine oxine (99mTc-HMPAO) leucocytes using a numerical grading system (scores 0-3). A 4-h series of scintigrams showed a significant correlation with both histological and macroscopical assessment of disease activity (rho = 0.850, P less than 0.001 and rho = 0.773, P less than 0.001, respectively). Sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

1993
1993
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(17 citation statements)
references
References 11 publications
0
16
1
Order By: Relevance
“…This is in agreement with the findings in a large series of children in whom no false-positive uptakes were observed in the terminal ileum. 32 Nonspecific bowel activity, unrelated to inflammatory bowel disease, has in other studies been observed in the small bowel and proximal colon as early as 30 minutes after injection of technetium-99m exametazime-labeled cells 33 and been found in about 15% of subjects within the first hour. 29,34 In other series, such activity has first been seen on 2-hour images in 7% or on 3-4-hour images in 5%-28% of examinations 31,[35][36][37] or to occur only later than 3 hours.…”
Section: Discussionmentioning
confidence: 97%
“…This is in agreement with the findings in a large series of children in whom no false-positive uptakes were observed in the terminal ileum. 32 Nonspecific bowel activity, unrelated to inflammatory bowel disease, has in other studies been observed in the small bowel and proximal colon as early as 30 minutes after injection of technetium-99m exametazime-labeled cells 33 and been found in about 15% of subjects within the first hour. 29,34 In other series, such activity has first been seen on 2-hour images in 7% or on 3-4-hour images in 5%-28% of examinations 31,[35][36][37] or to occur only later than 3 hours.…”
Section: Discussionmentioning
confidence: 97%
“…Compared with radiology and/or colonoscopy, scintigraphy is better able to detect disease extent [3]. On the other hand, non-specific bowel activity may cause false positive results [9]. Nonspecific intestinal uptake of 18 F-FDG is also a frequent finding on PET imaging of the abdomen.…”
Section: Discussionmentioning
confidence: 98%
“…Labeling granulocytes selectively using tecnetium-99 with hexamethyl-propylenamine oxime (HM-PAO) has been used with single-photon emission CT scanning for the study of intestinal inflammatory disease [66]. Its utility has also been proved in patients with EG, being more accurate than biopsy by endoscopy (Fig.…”
Section: Laboratory and Radiology Studiesmentioning
confidence: 99%